(untitled) (Historia, 2021)
The repositioning or realignment of history as a discipline in the field of the humanities (or social sciences) in the tertiary educational arena has been common in many of the most advanced liberal democracies of the world. In fact, in more than one university faculty, Fukuyama’s prophetic prediction in respect of the end of history has reverberated with astounding effects. The ending of the Cold War and the rapid development of informnation technology, as well as the rethink on government funding for certain fields of scientific endeavour have been instrumental in bringing about substantial changes.